Secondary School Enrolment and Teenage Childbearing: Evidence from Brazilian Municipalities - Martin Foureaux Koppensteiner; Jesse Matheson (Institute of Labor Economics (IZA), 2019)
This article investigates whether increasing secondary education opportunities influences childbearing among young women in Brazil. We examine a novel dataset reflecting the vast expansion of secondary education in Brazil between 1997 and 2009 and exploit variation in the introduction of schools across 4,884 municipalities to instrument for school enrolment. Our most conservative estimate suggests that for every 9.7 students enrolled there is one fewer teenage births. These findings are robust to a number of specifications and sensitivity tests. Our estimates imply that Brazil's secondary school expansion accounts for 34% of the substantial decline in teenage childbearing observed over the same period. We further look at heterogeneous effects across a number of municipal characteristics and discuss what these results suggest about the mechanisms underlying the school-childbearing relationship.
Keywords: I20; I26; J13; 330; secondary education; teenage childbearing; Brazil